O trabalho em laboratório na indústria do petróleo: do procedimento à competência - Freitas, Elizabeth Garcia de (Universidade Federal de São Carlos, 2011)
This dissertation has been realized in a chemistry analysis laboratory inside a Brazilian oil refinery. From the initial demand to project and build a new laboratory in a specific refinery, in order to attend the current work and the future work load increase, a key question was raised, the necessity to understand the laboratory work reality face the prescribed work. This case study has analyzed the labor in many subunits, or, Production Centers of the studied laboratory according to the Ergonomics Analysis of Work approach. It dares the necessity to understand the work organization, positioning the activity as central to the analysis, and unfold issues such the human relations at work. After doing the observations, transcriptions, analyses and auto-confrontation it was realized that, although the procedures prescription has been prescribed by the workers themselves, it was relatively simple and did not take into account the variety of activities. Therefore the workers resort of many means that were learned, created or incorporated to execute the tasks. These information, variability and situations are managed by the worker´s competencies, and are highlighted through specific skills, from previous and acquired knowledge, and from past experience. Due the competency to deal with work in this environment, it may be said that the workers adopt individual and collective strategies to manage the work, overcome the variability and the existing risks in order to produce reliable certifications ensuring health and productivity.
Keywords: Ergonomia; Indústria petrolífera; Trabalho - análise; Competência profissional; Indústria do petróleo; Trabalho em laboratório; Análise ergonômica do trabalho; Competência; Oil industrial; Laboratory work; Ergonomics work analysis; Competencies; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::ERGONOMIA